Effect of Different Collagen on Anterior Cruciate Ligament Transection and Medial Meniscectomy-Induced Osteoarthritis Male Rats - Felim, Jerrell; Chen, Chun-Kai; Tsou, David; Kuo, Hsiang-Ping; Kong, Zwe-Ling (Frontiers in Bioengineering and Biotechnology, 2022)
Osteoarthritis (OA) is a common type of arthritis disease characterized by degeneration of the articular cartilage and joint dysfunction. Various pharmacological and non-pharmacological techniques have been used to manage these diseases. Due to the diverse therapeutic properties of marine collagen, it has received considerable attention in its pharmacological application. Thus, the purpose of this study was to compare the efficacy of jellyfish collagen, collagen peptide, other sources of marine collagen, and glycine in treating OA. In the OA rats model, an anterior cruciate ligament transection combined with medial meniscectomy surgery (ACLT + MMx) was used to induce osteoarthritis in rats. Two weeks before surgery, male Sprague-Dawley rats were fed a chow-fat diet. After six weeks of treatment with collagen, collagen peptide, and glycine, results show that they could inhibit the production of proinflammatory cytokines and their derivatives, such as COX-2, MMP-13, and CTX-II levels, therefore it can attenuate cartilage degradation. Moreover, collagen peptides can promote the synthesis of collagen type II in cartilage. These results demonstrate that collagen and glycine have been shown to have protective properties against OA cartilage degradation. In contrast, collagen peptides have been shown to have cartilage regeneration but less protective properties. Jellyfish collagen peptide at a dose of 5 mg/kg b.w. has the most significant potential for treating OA because it protects and regenerates cartilage in the knee.